Erie County Study, 1940 - Lazarsfeld, Paul F. ([Verlag nicht ermittelbar], 1984)
This data collection contains information on changes in voting intentions and attitudes among voters in Erie County, Ohio, in 1940. The investigators were most interested in studying the dynamics of the formation, change, and development of public opinion and political attitudes. Special efforts were made to follow the changes in voting intentions and to gather data on the possible intervening factors in the attitudinal change process. Data are provided on respondents' perceptions of the social and ideological differences between the parties, their participation in the campaign, political information gathering and networks, use of the news media, voting intentions, and choice of presidential candidates. Other items provide information on the role of personal relationships and social groups, the political and voting history of the respondents and their family, personality measures, issue opinions, the influence of family and friends, the news media, and political rallies in respondents' political opinion-formation and change. Additional items probe respondents' views of the United States' sale of ammunition to nations at war, Roosevelt and Willkie as presidential candidates, passage of the conscription bill, the news media, and the 1940 election. Demographic items specify age, place of birth, sex, marital status, occupation, education, religion, club and labor union membership, and nationality.